PENGEMBANGAN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) BERBASIS KOOPERATIF TIPE TGT MATERI GETARAN DAN GELOMBANG - Renita Aprilia; Nur Kuswanti; Oktaffi Arinamanasikana (Discovery : Jurnal Ilmu Pengetahuan, 2021)
This research is initialized by the teacher-centered science learning process, the limited use of learning tools in the form of lesson plans, the less varied use of learning models and games making students understand easily. The objectives are describing: the process of developing TGT cooperative-based RPP on vibration and wave material and the feasibility of TGT-based cooperative learning plans on material vibrations and waves. The development model used was ADDIE model consisting of 5 stages, namely Analysis, Design, Development, Implementation and Evaluation but the Implementation stage was not implemented. The validity data used RPP validation sheet. This development research resulted in a TGT-based cooperative learning plan (RPP) product. The results indicated that the process of developing a lesson plan refers to the ADDIE development model. Analysis consisted of 3 steps covering needs analysis, curriculum analysis and material analysis. Design was carried out by collecting references and compiling a cooperative RPP based on the TGT type. Development was assessed by experts consisting of 3 validators, namely 2 lecturers of natural science education courses and 1 junior high school teacher. From the results of the assessment obtained validity assessments as well as input and suggestions from the validator used to produce the final RPP product. The Evaluation step was carried out at each stage. The quality of the TGT cooperative learning based learning plan on vibration and wave material developed based on validity was declared feasible to use because the validation results obtained a score of 4.78 with a very valid category. Keywords: Development of lesson plan, Cooperative Learning, TGT (Teams Games Tournament), ADDIE development model.